2020
DOI: 10.3389/fpubh.2020.553850
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Endocrine-Disrupting Chemical Exposure: Role in Non-Communicable Diseases

Abstract: The exponential growth of pollutant discharges into the environment due to increasing industrial and agricultural activities is a rising threat for human health and a biggest concern for environmental health globally. Several synthetic chemicals, categorized as potential environmental endocrine-disrupting chemicals (EDCs), are evident to affect the health of not only livestock and wildlife but also humankind. In recent years, human exposure to environmental EDCs has received increased awareness due to their as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
122
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 240 publications
(126 citation statements)
references
References 303 publications
(306 reference statements)
0
122
0
4
Order By: Relevance
“…Beyond informing our understanding of endocrine regulation during post-embryonic skin development, our work has potential implications for environmental toxicology. Ever increasing discharge of endocrine disrupting pollutants is a pressing concern that affects natural environments and human health (Kumar et al, 2020). Although analytical chemistry methods are very sensitive in detecting endocrine disrupting compounds in environmental samples, these methods require advanced instrumentation and sophisticated sample preparation.…”
Section: Discussionmentioning
confidence: 99%
“…Beyond informing our understanding of endocrine regulation during post-embryonic skin development, our work has potential implications for environmental toxicology. Ever increasing discharge of endocrine disrupting pollutants is a pressing concern that affects natural environments and human health (Kumar et al, 2020). Although analytical chemistry methods are very sensitive in detecting endocrine disrupting compounds in environmental samples, these methods require advanced instrumentation and sophisticated sample preparation.…”
Section: Discussionmentioning
confidence: 99%
“…However, systemic reviews and meta-analyses focusing on human studies have demonstrated inconsistent results ( Kahn et al, 2020 , Lee, 2018 ). While the ability of EDCs to promote adverse modifications of endocrine homeostasis in human and wildlife raises serious concerns about their potential health impact, uncertainty remains around a definitive link between EDCs and reproductive disorders and mechanistic links between the two ( Bergman et al, 2013 , Bergman et al, 2015 , Combarnous and Nguyen, 2019 , Dietrich et al, 2013 , Gore et al, 2013 , Kortenkamp et al, 2012 , Kumar et al, 2020 , Lamb et al, 2015 , Rhomberg et al, 2012 , Zoeller et al, 2014 ). Swaen et al ( Swaen et al, 2018 ) argue that profound changes in human reproduction have a major impact on the incidence of reproductive disorders.…”
Section: Establishing the Link Between Edcs And Hypospadiasmentioning
confidence: 99%
“…In fact, a number of EDCs have been increasingly reported to be linked with human health problems especially female reproductive disorders in recent years [ 19 ]. Results from several literature indicated that BPA and phthalates played negative roles in thyroid function on the basis of different thyroid hormone levels [ 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, BPA and phthalates—as oestrogen-mimicking EDCs—are thought to be responsible for inducing the occurrence and progression of many oestrogen-dependent cancers by binding to oestrogenic receptors, which are important evolution-related transcription factors related to many critical biological processes. Such actions probably play a considerable role in human breast carcinogenesis [ 19 , 31 ]. Amongst the multitudinous hormone-dependent cancers related to BPA and phthalates exposure, breast cancer is the most important issue that should be placed more attention.…”
Section: Introductionmentioning
confidence: 99%